Synchronization of Estrus by ‘Buck Effect’ and PGF2α Treatment in Surti Does - Khasatiya, Chaudhari; Chaudhari, NF; Tyagi, KK; Kharadi, VB; Atara, VB (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
This investigation was aimed to study the influence of buck and PGF2α treatment on estrus synchronization in Surti does. Apparently healthy non-pregnant Surti does (n=18) were identified from the flock by Ultrasonography. They were evenly divided into 3 groups, 6 does in each group. The does of Treatment T1 group were teased with a sexually-active-apronized buck; the does of Treatment T2 group were treated with PGF2α, i.e., Inj. Lutalyse® @ 7.5 mg/doe IM twice, i.e. on day 0th and 11th, while the does of Control group T3 were kept without any treatment. The behavioural estrus was successfully synchronized by double injection of PGF2α at 11 days apart, as well as by buck effect in T2 and T1 groups, respectively. The induction of estrus was observed cent per cent in all the groups within one month. The mean time intervals between start of treatment and onset of estrus differed significantly between T1 (5.83±2.20 d) and T3 (14.67±2.76 d) groups. However, the mean duration of estrus was 29.83±0.91, 27.50±1.23 and 28.67±1.28 hrs and the mean number of services per conception was found 1.33±0.33, 1.50±0.50 and 1.33±0.33 for T1, T2 and T3 groups of Surti does, respectively, none differ significantly (p>0.05) between the groups. There was no significant difference in conception rates at first service amongst the groups (83.33%). The 17 does among 18 does (94.44 %) from all the three groups conceived within three services, irrespective of treatment groups. It was found that the buck effect appeared to be as effective as conventional PGF2α treatment in Surti does for synchronization of estrus.
Keywords: Buck effect; Goat; PGF2 α; Synchronization